Mechanical characterisation of heat resistant power plant materials by creep and fatigue testing in controlled gas atmospheres. Issue 1 (January 2014) - Olbricht, J.; Lippmann, T.; Klingelhöffer, H.; Rehmer, B.; Skrotzki, B.
<x xml:space="preserve">Abstract</x> The continuing increase of steam parameters of fossil fuelled high efficiency power plants and new combustion concepts for the capture and storage of carbon dioxide lead to harsher service conditions for the components and structural materials of such facilities. The present work introduces a test concept that allows testing of candidate materials under simultaneous mechanical and corrosive loading. The material's reaction can be directly investigated under simulated temperature, load and corrosion conditions of modern installations. First results obtained for different heat resistant steels suggest a strong influence of the environmental medium on the fatigue and creep behaviour. Such findings complement the data that is available from the classical qualification process of the materials and may support the material selection for new power plant installations.